Challenges and Opportunities for Pharmaceutical Enterprises in Adopting International Accounting Standards for Medicines - T., Sattorov T. (Research Parks Publishing LLC, 2023)
This scientific article examines the challenges and opportunities for pharmaceutical enterprises in Uzbekistan in adopting international accounting standards for medicines. The study compares the accounting standards and practices in Uzbekistan with international standards, such as International Financial Reporting Standards (IFRS) and United States Generally Accepted Accounting Principles (US GAAP), and identifies potential benefits and drawbacks of adoption. Interviews with stakeholders, including accountants, auditors, and regulators, were conducted to gather insights and perspectives on the topic. The results show that adoption of international accounting standards can improve transparency, comparability, and credibility of financial statements, but may also require significant resources and expertise. The study provides recommendations for pharmaceutical enterprises in Uzbekistan to address the challenges and seize the opportunities in adopting international accounting standards for medicines.